2022
DOI: 10.3390/diagnostics12123085
|View full text |Cite
|
Sign up to set email alerts
|

Development of in House ELISAs to Detect Antibodies to SARS-CoV-2 in Infected and Vaccinated Humans by Using Recombinant S, S1 and RBD Proteins

Abstract: (1) Background: The aim of this study was to produce in-house ELISAs which can be used to determine SARS-CoV-2-specific antibody levels directed against the spike protein (S), the S1 subunit of S and the receptor binding domain (RBD) of S in SARS-CoV-2 vaccinated and infected humans. (2) Methods: Three in-house ELISAs were developed by using recombinant proteins of SARS-CoV-2, namely the S, S1 and RBD proteins. Specificity and sensitivity evaluations of these tests were performed using sera from SARS-CoV-2-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…ELISA results revealed that 76.5% (153/200) and 73% (146/200) of the patient sera recognized the full spike1 protein (commercial S1-EU kit) or its receptor binding domain (in-house RBD/S1-IH kit), respectively. This shows the similar performance of both ELISA assays, with the in-house version being economically affordable to measure antibody responses in the SARS-CoV-2-infected as well as vaccinated individuals from early at 2 weeks to a long time post-infection [21,22].…”
Section: Discussionmentioning
confidence: 66%
“…ELISA results revealed that 76.5% (153/200) and 73% (146/200) of the patient sera recognized the full spike1 protein (commercial S1-EU kit) or its receptor binding domain (in-house RBD/S1-IH kit), respectively. This shows the similar performance of both ELISA assays, with the in-house version being economically affordable to measure antibody responses in the SARS-CoV-2-infected as well as vaccinated individuals from early at 2 weeks to a long time post-infection [21,22].…”
Section: Discussionmentioning
confidence: 66%